How an Effective Strategy For Implementing Ecopreneurship in Batik MSMEs? Analythical Hierarchy Process Approach - Widjajanti, Kesi; Sugiyanto, Eviatiwi Kusumaningtyas; Widyaevan, Dea Aulia; Sari, Anisa Rachma (Universitas Negeri Semarang, 2024)
This study aims to formulate an effective strategy for implementing ecopreneurship in batik MSMEs. The sampling technique used purposive sampling to ensure that the selected samples have a direct relationship with ecopreneurship practices. Key respondents include MSME owners, environmental experts, academics, and policy makers in the MSME sector. Data collection was carried out through structured interviews, questionnaires, and documentation studies. The questionnaire was designed to evaluate the priorities of respondents. The results of the study indicate that the first priority strategy alternative in the strategy for implementing ecopreneurship in batik MSMEs is the substitution of synthetic dyes for natural dyes with a local weight of 0.60 and a global weight of 0.24. This shows the urgency to reduce environmental impacts through the use of environmentally friendly raw materials. The development of recycled raw materials and the processing of liquid waste into new products are ranked second because of the relevance of both in supporting efficiency and sustainability